2016
DOI: 10.22492/ijpbs.2.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress and Police Burnout: Moderating Roles of Gender and Marital Status

Abstract: Previous studies on occupational burnout among police personnel did not pay enough attention to how gender and marital status may influence the connection between job stress and occupational burnout, especially where cultural beliefs direct gender and marital issues in relation to work, such as Nigeria. This study, therefore, investigated the extent to which gender and marital status moderate the relationship between job stress and occupational burnout. Participants were 213 police personnel (male = 120; femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 35 publications
(83 reference statements)
5
15
0
Order By: Relevance
“…In regard to gender differences, as shown in this research, there were significant differences between women’s and men’s burnout measurement. Research showed that, due to their double roles, traditional trends and responsibilities, women are at higher risk of burnout [ 39 , 61 , 62 , 63 , 64 ]. Therefore, women police officers; mental health risks should be monitored carefully and interventions involving sports and leisure activities should be included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to gender differences, as shown in this research, there were significant differences between women’s and men’s burnout measurement. Research showed that, due to their double roles, traditional trends and responsibilities, women are at higher risk of burnout [ 39 , 61 , 62 , 63 , 64 ]. Therefore, women police officers; mental health risks should be monitored carefully and interventions involving sports and leisure activities should be included.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that women present higher work related stress and burnout than man due to their double roles [ 61 ]. Women are prone to a higher prevalence of burnout due to their responsibilities and traditional roles as mothers and wives [ 39 , 62 , 63 ] and job stress tended to result in higher level of occupational burnout in female than in male police personnel [ 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second possible reason might be connected with consideration of gender-specific and socio-cultural norms, which expect females to perform the roles of a mother and wife in spite of their job roles (Ogungbamila & Fajemirokun, 2016). Apart from the stated reasons, female police personnel, especially those that were married, might have benefitted from preferential treatments in posting and assignment of duties.…”
Section: Discussionmentioning
confidence: 99%
“…Gender defines an individual status as either male or female. It spells out those social, cultural, and physiological roles that are specific to males and females in a social context (Fapohunda, 2014;Odedokun, 2015;Ogungbamila & Fajemirokun, 2016). Results from past studies on the role of gender on police personnel's quality of work-life have shown that male police personnel had greater quality of work-life in the sense that they experienced less psychological distress and were able to withstand stress than their female counterparts (Nair & Joseph, 2013;Ogungbamila & Idemudia, 2016).…”
Section: Gender and Quality Of Work-lifementioning
confidence: 99%
“…Gender refers to individual status either as a male or female. It defines out those social, cultural, and physiological roles that are specific to males and females in a social context (Fapohunda, 2014;Odedokun, 2015;Ogungbamila & Fajemirokun, 2016). Ekot (2016) found in his study a significant link among gender and all typology of abuse, i.e.…”
Section: Socio Demographic Factors (Gender and Income) And Elder Abusementioning
confidence: 99%